ARCHITECTURE OF THE MEDRESE OF KHOREZM AND THEIR PLANNING FEATURES - Alieyva Robiabonu, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article examines specific design solutions (from the Middle Ages) of the Khorezm school of madrasas in the architectural context. It studies the typology and varieties of madrasas that have been preserved and are still used in the construction of modern Islamic cultural centers, as well as the differences and features of local architectural schools. The article identifies the patterns of formation and development of the Khorezm architectural school. It also examines the influence of the natural conditions of the region and urban planning concepts on the development of Khorezm religious architecture in Uzbekistan.